The Influence Of Feeding Habbits On The Incidence Of Stunting - Aprillia Ayu Shinta Yuka; Yunetra Franciska; Jasmi Jasmi; Asri Noviyanti (Poltekkes Kemenkes Palembang, 2023)
Stunting emerges as a consequential nutritional challenge among toddlers, resulting from prolonged exposure to malnutrition. Rooted in familial caregiving practices, particularly feeding habits, this study delves into the nexus between feeding behaviors and the prevalence of stunting among impoverished families in Palembang. Employing a quantitative approach through a Cross Sectional Study, the research encompasses 110 mothers with children aged 24-59 months from economically disadvantaged backgrounds in Palembang. The findings underscore a noteworthy correlation between feeding habits and the incidence of toddler stunting, yielding a significant p-value of 0.000 and an Odds Ratio of 14.389. Noteworthy feeding practices influencing stunting include the administration of colostrum at birth (p-value = 0.020), diversified feeding (p-value = 0.000), nutritionally balanced meals (p-value = 0.003), maternal food preparation (p-value = 0.005), consistent snack provision (p-value = 0.002), age-appropriate portion adjustments (p-value = 0.042), offering food choices during boredom (p-value = 0.001), active feeding assistance (p-value = 0.001), maternal efforts to encourage eating (p-value = 0.000), and fostering an interest in eating (p-value = 0.007). Comparatively, non-stunted toddlers exhibit superior feeding habits when juxtaposed with their stunted counterparts within similar economic circumstances. This research illuminates the pivotal role of feeding practices in mitigating or exacerbating toddler stunting, thereby advocating for targeted interventions to enhance nutritional well-being in vulnerable populations.